2006
DOI: 10.1016/j.febslet.2005.12.091
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular adenine nucleotides inhibit the release of major monocyte recruiters by human monocyte‐derived dendritic cells

Abstract: Extracellular ATP is known to affect the maturation of monocyte-derived dendritic cells mainly by regulation of cytokines and costimulatory molecules. The present study describes the inhibition of MCP-1 (CCL2) and MIP-1a (CCL3) release by human monocyte-derived dendritic cells in response to adenine nucleotides. Our pharmacological data support the involvement of P2Y 11 and P2Y 1 purinergic receptors in the downregulation of these major monocyte recruiters. Migration assays have demonstrated that supernatants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
(31 reference statements)
2
17
0
Order By: Relevance
“…We have shown that NECA has an impressive effect on gene expression in LPSstimulated murine BMDC. Some regulations are similar to what has been observed in ATPcS-treated human DC: up-regulation of TSP-1 [11] and VEGF [43], down-regulation of CCL2 and CCL3 [44]. On the contrary, some regulations were not observed in murine BMDC, e.g.…”
Section: Discussionsupporting
confidence: 50%
“…We have shown that NECA has an impressive effect on gene expression in LPSstimulated murine BMDC. Some regulations are similar to what has been observed in ATPcS-treated human DC: up-regulation of TSP-1 [11] and VEGF [43], down-regulation of CCL2 and CCL3 [44]. On the contrary, some regulations were not observed in murine BMDC, e.g.…”
Section: Discussionsupporting
confidence: 50%
“…PGE 2 effects on DC maturation are likely to result from activation of the EP2/EP4 receptors (14). Many of the effects of ATP␥S on MoDCs, such as its effect on CD83 expression and TSP-1 release, are reproduced by forskolin or dibutyryl-cAMP, demonstrating their action through cAMP elevation (4,5,11,14).…”
Section: Discussionmentioning
confidence: 99%
“…We first performed a selection of sequences regulated at least 2-fold for at least for one agent and one time point (see Table S1 in the supplementary data). 5 Among these 3,512 regulated sequences, 1,896 oligonucleotides were regulated at least 2-fold by ATP␥S and only 97 oligonucleotides were regulated at least 2-fold by PGE 2 . From these experiments, it thus appeared that ATP␥S was able to induce a very wide and early gene expression profile in MoDCs.…”
Section: Comparison Of Atp␥s and Pge 2 Gene Expression Profiles In Modcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has been presented that P2Y 1 receptors are involved in allergic airway inflammation, which could be at least partly explained by its role in the regulation of dendritic cell maturation (Maitre et al, 2008). Extracellular adenine nucleotides inhibit the release of major monocyte recruiters by human monocytederived dendritic cells and pharmacological data support the involvement of P2Y 11 and P2Y 1 purinergic receptors (Horckmans et al, 2006). In a recent article, it is proposed that purinergic signaling via P2Y 2 receptors in the respiratory epithelium is a critical sensor for airway exposure to airborne allergens, which may provide novel opportunities to dampen hypersensitivity in the Th2-type immune responses in asthma (Kouzaki et al, 2011).…”
Section: A Asthmamentioning
confidence: 99%